Do Biobank Recall Studies Matter? Long-Term Follow-Up of Research Participants With Familial Hypercholesterolemia - Nurm, Miriam; Reigo, Anu; Nõukas, Margit; Leitsalu, Liis; Nikopensius, Tiit; Palover, Marili; Annilo, Tarmo; Alver, Maris; Saar, Aet; Marandi, Toomas; Ainla, Tiia; Metspalu, Andres; et al. (Frontiers in Genetics, 2022)
Recall-by-genotype (RbG) studies conducted with population-based biobank data remain urgently needed, and follow-up RbG studies, which add substance and novelty to this research approach, remain rare. In such studies, potentially disease-related genotypes are identified and individuals with those genotypes are recalled for consultation to gather more detailed clinical phenotypic information and explain to them the meaning of their genetic findings. Familial hypercholesterolemia (FH) is among the most common autosomal-dominant single-gene disorders, with a global prevalence of 1 in 500. Untreated FH leads to lifelong elevated LDL cholesterol levels, which can cause ischemic heart disease, with potentially fatal consequences at a relatively early age. In most cases, the pathogenesis of FH is based on a defect in one of three LDL receptor-related genes – APOB, LDLR, and PCSK9. We present the first long-term follow-up RbG study of FH, conducted with Estonian Biobank participants (34 recalled participants from a pilot RbG study and 291 controls harboring the same APOB, LDLR, and PCSK9 variants that were included the pilot study). The participants’ electronic health record data (FH-related diagnoses, lipid-lowering treatment prescriptions) and pharmacogenomic risk of developing statin-induced myopathy were analyzed. A survey was administered to recalled participants to discern the impact of the knowledge of their genetic findings on their lives 4-6 years later. Significant differences in FH diagnoses and lipid-lowering treatment prescriptions were found between the recalled participants and controls. We highlight the need for more consistent lipid-lowering treatment adherence and encourage the performance of more follow-up RbG studies.